Use of Anodic TiO2 Nanotube Layers as Mesoporous Scaffolds for Fabricating CH3NH3Pbl3 Perovskite-Based Solid-State Solar Cells - Salazar, Raul; Altomare, Marco; Lee, Kiyoung; Tripathy, Jyotsna; Kirchgeorg, Robin; Nguyen, Nhat Truong; Mokhtar, Mohamed; Alshehri, Abdelmohsen; Al-Thabaiti, Shaeel A.; Schmuki, Patrik (ChemElectroChem, 2015)
We optimize the deposition of CH3NH3PbI3 perovskite into mesoporous electrodes consisting of anodic TiO2 nanotube layers. By a simple spin-coating approach, complete filling of the tube scaffolds is obtained, which leads to interdigitated perovskite structures in conformal contact with the TiO2 tube counterparts. Such assemblies can be used as solid-state solar cells in a hole-transporting-material-free configuration, that is, the tube scaffold serves as electron collector and blocking layer, while the perovskite acts as visible-light absorber and hole-transporting material. We show that the complete filling of the tube scaffold with the perovskite is essential to improve the solar cell efficiency.
EAM Import::2019-03-12